Advance care planning in adults with oral cancer: Multi‐institutional cross‐sectional study. Issue 5 (8th September 2021) - Forner, David; Lee, Daniel J.; Grewal, Rajan; MacDonald, Jenna; Noel, Christopher W.; Taylor, S. Mark; Goldstein, David P.
Abstract: Purpose: Patients undergoing head and neck surgery are often elderly and frail with significant comorbidities. Discussion and documentation of what patients would desire for end‐of‐life care and decision‐making is, therefore, essential for delivering patient‐centered care. Materials and Methods: This was a retrospective, cross‐sectional study of patients undergoing surgery for head and neck cancer at two large, academic, tertiary care centers in Canada. Advance care planning was defined as any documentation of advance directives, resuscitation orders, or end‐of‐life care preferences. Results: Among 301 patients, advance care planning was documented for 31 (10.3%). Patients with locally advanced disease (T3+) were twice as likely to have advance care planning documentation compared to those with early disease (RR 1.97, 95%CI [0.98, 3.97]). Conclusions: In this multi‐institutional cross‐sectional study of two large academic centers, we have demonstrated that advance care planning and documentation is overall poor in patients undergoing surgery for oral cancer. These findings may have health policy implications, as advance care planning is associated with increased patient and provider satisfaction and improved alignment of patient goals and care delivered. Future work will investigate barriers and facilitators to advance care‐planning documentation in this setting.